2013
DOI: 10.1002/ijc.28347
|View full text |Cite
|
Sign up to set email alerts
|

Sarcosine and other metabolites along the choline oxidation pathway in relation to prostate cancer—A large nested case–control study within the JANUS cohort in Norway

Abstract: Methyl group donors and intermediates of one-carbon metabolism affect DNA synthesis and DNA methylation, and may thereby affect prostate carcinogenesis. Choline, the precursor of betaine, and the one-carbon metabolite sarcosine have been associated with increased prostate cancer risk. Within JANUS, a prospective cohort in Norway (n 5 317,000) with baseline serum samples, we conducted a nested case-control study among 3,000 prostate cancer cases and 3,000 controls. Using conditional logistic regression, odds ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 41 publications
0
30
1
Order By: Relevance
“…Elevated sarcosine levels in urine (Sreekumar et al, 2009) and serum (Koutros et al, 2013) have been associated with prostate cancer progression, although this relation has not been observed in other reports (de Vogel et al, 2014; Jentzmik et al, 2011). Elevated urine sarcosine levels were also associated with incident type 2 diabetes (Svingen et al., 2016), while low levels of sarcosine in blood have been linked with advanced arteriosclerosis (Hasokawa et al, 2012) and several neurological disorders, including neuropathic pain (Barthel et al, 2014), cerebral ischemia (Pinto et al, 2014), seizure (Socała et al, 2010), and Parkinson disease (Tsai et al, 2014).…”
Section: Discussionmentioning
confidence: 82%
“…Elevated sarcosine levels in urine (Sreekumar et al, 2009) and serum (Koutros et al, 2013) have been associated with prostate cancer progression, although this relation has not been observed in other reports (de Vogel et al, 2014; Jentzmik et al, 2011). Elevated urine sarcosine levels were also associated with incident type 2 diabetes (Svingen et al., 2016), while low levels of sarcosine in blood have been linked with advanced arteriosclerosis (Hasokawa et al, 2012) and several neurological disorders, including neuropathic pain (Barthel et al, 2014), cerebral ischemia (Pinto et al, 2014), seizure (Socała et al, 2010), and Parkinson disease (Tsai et al, 2014).…”
Section: Discussionmentioning
confidence: 82%
“…Betaine is also very beneficial to osmotically stressed cells (Hoffmann et al 2013) and methyl group donors, such as betaine, influence DNA synthesis and methylation (de Vogel et al 2014). Methionine synthase and methylenetetrahydrofolate reductase play vital roles in the maintenance of correct DNA methylation levels because they are involved in the metabolism of the methyl group (Weiner et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies led to interest in sarcosine as a prostate cancer biomarker but in many of such studies, results have been conflicting; some indicated higher risk associated with higher levels of sarcosine and others, a lower risk 9,10 . In order to definitively assess the potential of serum sarcosine for further study, we are reporting a preliminary data for its reference value in our locality.…”
Section: Discussionmentioning
confidence: 99%